Physical properties of Robusta coffee beans - Ghosh, B.N. (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2025)
The physical properties of the two important commercial types of coffee beans, Arabica and Robusta, from the wet parchment to the dry or green bean stage are of interest in developing the specialized processing machinery and equipment for their wet processing. While values for the better quality Arabica coffee has been reported earlier (2), comparative values for Robusta, traditionally processed by the dry method but now wet processed in increasing quantities, are reported in the present paper. The methods used and the results obtained are described. A comparative study of the Arabica and Robusta types indicated that physical properties like weight, volume, density and mesh size distribution were different